Women Entrepreneurship: A Case Study of Siddharthnagar District - Gupta, Kavita (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The rise of the spirit of female entrepreneurs is established over the years tend to be good about the role of jobseekers instead of jobseekers, though. The relative share of women among the total entrepreneurs in India is a tenth Siddharthnagar represent a significant proportion of the total enterprising women equally in the world population. Socio-economic characteristics of respondents now show that increasing the participation of women in social awareness education and training. Female entrepreneurs will facilitate the transfer of the service sector than in trade and industry. So I get more and more female businesswoman. And it plays a positive role in the economy. Today, the development of female entrepreneurs is in the region have no fear, and can be lively and optimistic. Keywords: Female Entrepreneurs, Socio-Economic, Unfavorable, Financial Support.